1998
DOI: 10.1086/515383
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Polymerase Chain Reaction to Predict Occurrence of Symptomatic Cytomegalovirus Infection and Assess Response to Ganciclovir Therapy in Renal Transplant Recipients

Abstract: Cytomegalovirus (CMV) DNA levels were measured by quantitative-competitive polymerase chain reaction (PCR) in weekly leukocyte samples from 50 renal transplant recipients, including 23 with symptomatic and 27 with asymptomatic CMV infection. Peak and week 4 CMV DNA levels were higher in symptomatic subjects (P = .07 and .02, respectively). In a logistic regression model, the logarithm of the week 4 level independently predicted symptomatic infection (odds ratio, 1.78 for a 1 log10 increase; 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
1
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 32 publications
4
75
1
4
Order By: Relevance
“…33 Assessment of viral load kinetics may provide a tool for stratifying risk profiles for HCMV disease and help reduce the considerable rate of antiviral overtreatment. Although a correlation between peak viral load and HCMV disease development was noticed by several other groups in patients after solid organ transplantation and HIV patients, 28,[34][35][36][37][38][39] discordant results have been reported in SCT patients. 15,16,22,31,40 For abbreviations, see Table 1 footnote.…”
Section: Discussionmentioning
confidence: 85%
“…33 Assessment of viral load kinetics may provide a tool for stratifying risk profiles for HCMV disease and help reduce the considerable rate of antiviral overtreatment. Although a correlation between peak viral load and HCMV disease development was noticed by several other groups in patients after solid organ transplantation and HIV patients, 28,[34][35][36][37][38][39] discordant results have been reported in SCT patients. 15,16,22,31,40 For abbreviations, see Table 1 footnote.…”
Section: Discussionmentioning
confidence: 85%
“…Similar conclusions have been drawn from recent studies involving other immunosuppressed cohorts. 38,[42][43][44][45][46][47][48][49][50] Quantitative PCR for CMV appears to be an effective diagnostic tool in identifying patients with disease. In addition, PCR detection of DNA targets is less sensitive to sample handling than other diagnostic tests.…”
Section: Predictive Value Of Quantitative Pcrmentioning
confidence: 99%
“…Similar results have been reported for other immunosuppressed populations. 34,36,45,46,50,55,70 Management of anti-CMV therapy using quantitative PCR could potentially reduce the incidence of therapy-related side effects and therapy costs if disease could be controlled with a more limited course of antiviral therapy. EBV levels were also found to respond to changes in medication in the patient with lympadenopathy.…”
Section: Predictive Value Of Quantitative Pcrmentioning
confidence: 99%
“…There have been many studies evaluating the clinical utility of a PCR-based assay for detection of HCMV DNA. [19][20][21] Many of these investigations have shown that the assay may be sensitive but has not enough clinical specificity to detect HCMV in patients who do not have active HCMV disease. However, we demonstrated a significant association between double primer PCR assay results of PMN leukocytes and antigenemia results in relation to clinical status of BMT patients.…”
Section: Discussionmentioning
confidence: 99%